Case Report: An “Immune-Cold” EGFR Mutant NSCLC With Strong PD-L1 Expression Shows Resistance to Chemo-Immunotherapy - Zhao, Qian; Zhang, Xue; Ma, Qiang; Luo, Nuo; Liu, Zhulin; Wang, Renyuan; He, Yong; Li, Li (Frontiers in Oncology, 2022)
Long-term survival benefit has been noticed in non-small-cell lung cancer (NSCLC) patients treated with immune checkpoint inhibitors (ICIs), such as PD-1 inhibitors. However, it is still controversial whether patients with EGFR-activating mutations may benefit from ICIs. Recently, in stage ⅢA NSCLC, chemo-immunotherapy has led to significant pathological response, yet patients with the presence of known EGFR mutations were excluded from some randomized trials of neoadjuvant therapy. Herein, we report a case of a 50-year-old female patient, who was initially diagnosed as stage ⅢA lung squamous cell carcinoma. Immunohistochemistry analysis showed that the patient presented with high PD-L1 expression. Then, chemo-immunotherapy was given to the patient but the disease progressed quickly with distant metastasis. A re-biopsy revealed a poorly differentiated lung adenocarcinoma together with EGFR p.L858R mutation. Then the patient received gefitinib, which resulted in significant regression of primary lung lesion. A detailed examination of pre-treatment tumor sections demonstrated rare infiltration of CD8+ T cells, indicating that the current patient presented with an “immune-cold” microenvironment, which might explain the primary resistance to chemo-immunotherapy. Taken together, our case indicated that comprehensive detection of PD-L1 expression, driver gene status, together with tumor immune microenvironment, may offer a better prediction of treatment efficacy.